PENGARUH PERHATIAN ORANG TUA TERHADAP PRESTASI BELAJAR SISWA KELAS XI DI SMA SANDIKTA - Raland Belive Daeli (Arthaniti Studies, 2026)
This study examines the influence of parental attention on the academic achievement of 11th-grade students at SMA Sandikta Bekasi in the 2025/2026 academic year. Using an associative quantitative method, a sample of 71 students was selected from a population of 241. Data were collected through questionnaires and analyzed using simple linear regression. The results show no significant effect, with an R Square value of 0.000 and a significance level of 0.893.